Arm balancing control and experimental validation of a grid connected MMC with pulsed DC load - Jankovic, Marija; Costabeber, Alessando; Watson, Alan James; Clare, Jon C. (Institute of Electrical and Electronics Engineers, 2017)
This paper focuses on the operation of a grid connected Modular Multilevel Converter (MMC) supplying a pulsed DC load. The goal is to achieve minimum AC power fluctuation despite the high power fluctuation present on the DC side. The MMC has been selected for its inherent ability to decouple AC and DC current controllers. How¬ever, if no additional provisions are taken, the pulsed load causes imbalance of cell capacitor voltages between upper and lower arm in each phase. The paper presents the the-oretical analysis of the imbalance problem, and proposes a simple arm balancing controller to enable the operation of the converter under pulsed DC load. The effectiveness of the controller has been successfully verified on a 7 kW MMC experimental prototype with a 3 kA pulsed DC load.